Pengabdian Masyarakat: Penerapan Metode At-Tartil terhadap Peningkatan Kemampuan Baca al-Quran di TPQ Darussalam Kecamatan Krian, Sidoarjo - Nasirudin Al Ahsani; Diana Rahmawati Yuhro (Fakultas Dakwah IAIN Jember, 2022)
Often found also in the process of learning the Qur'an in various places is less effective. Tension, reticence, and egotism are some of these tendencies to distance. As a result, both teachers and students do not have the freedom to express themselves fully. Conditions like this will eventually lead to stagnation in the process of developing ideas, ideas and creativity in learning. Furthermore, teaching and learning activities will only be an activity that is monotonous, uninteresting, and becomes a boring routine. This service uses the Asset Based Community Development method. The location of the service was carried out at TPQ Darussalam, Krian sub-district, Sidoarjo district. This service aims to 1) identify and describe the application of the At-Tartil method, 2) identify and describe the improvement in the ability to read the Koran at TPQ Darussalam. This service was carried out at TPQ Darussalam Krian with the head of TPQ as an informant. Collecting data in the service this time using interviews, observation, and documentation. The results obtained in this service 1) the use of the At-Tartil method as an effective method yielded results at TPQ Darussalam, 2) there was an increase in the ability to read the Koran with the al-Tatwir method.